Prolactin and Psychopathology in Schizophrenia: A Literature Review and Reappraisal. (27th March 2014) - Rajkumar, Ravi Philip
Abstract : Secretion of the anterior pituitary hormone prolactin can be significantly increased by antipsychotic drugs, leading to a range of adverse effects in patients with schizophrenia. However, there is evidence from a variety of studies that prolactin may also be related to symptom profile and treatment response in these patients, and recent work has identified variations in prolactin secretion even in drug-free patients. In this paper, a selective review of all relevant studies pertaining to prolactin and schizophrenia, including challenge and provocation studies, is presented. The implications of this work are discussed critically. A tentative model, which synthesizes these findings and argues for a significant role for prolactin in the development of schizophrenia, is outlined.